2017
DOI: 10.31351/vol18isssuppl.pp1-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Anti-Inflammatory Effect of Pioglitazone in Experimental Models of Inflammation in Rats

Abstract: The antidiabetic thiozolidinediones (TZDs) a class of peroxisome proliferators-activated receptor (PPAR) ligands has recently been the focus of much interest for their possible role in regulation of inflammatory response. The present study was designed to evaluate the anti-inflammatory activity of pioglitazone in experimental models of inflammation in rats. The present study was conducted to evaluate the anti inflammatory effect of TZDs (pioglitazone 3mg/Kg) on acute, sub acute and chronic model of inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…As shown in (Table 1 and Figure 1a), edema began to develop rapidly within thirty minutes and reaches its maximum at the first-hour post-injection in all egg albumininjected rats (except diclofenac treated rats, which has maximum edema within thirty minutes after the induction of inflammation). These outcomes are in agreement with previous research, where egg albumin injection was reported to cause a significant, time-dependent increase in rat's paw thickness [2,14,15]. Edema is one of the fundamental parameters of acute inflammation and resulted from the release of many proinflammatory mediators from cells involved in the inflammatory response.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…As shown in (Table 1 and Figure 1a), edema began to develop rapidly within thirty minutes and reaches its maximum at the first-hour post-injection in all egg albumininjected rats (except diclofenac treated rats, which has maximum edema within thirty minutes after the induction of inflammation). These outcomes are in agreement with previous research, where egg albumin injection was reported to cause a significant, time-dependent increase in rat's paw thickness [2,14,15]. Edema is one of the fundamental parameters of acute inflammation and resulted from the release of many proinflammatory mediators from cells involved in the inflammatory response.…”
Section: Resultssupporting
confidence: 93%
“…Among the various available methods utilized for the screening of anti-inflammatory agents, one of the most commonly used is the ability of the tested compounds to inhibit the edema induced in the rats' paws upon injection of the phlogistic agent [12]. Paw edema induced by egg albumin is a highly reproducible and widely studied model of acute inflammation [13][14][15]. Edema, erythema, and hyperalgesia have been found to develop instantly following the injection of egg albumin into the rats' hind paw, due to the pro-inflammatory action of various mediators and ROS generated at the site of the tissue injury or by infiltrating cells [16].…”
Section: Introductionmentioning
confidence: 99%